2022
DOI: 10.3389/fpubh.2022.881303
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mindfulness Yoga in Children With School Refusal: A Study Protocol for an Exploratory, Cluster-Randomized, Open, Standard Care-Controlled, Multicenter Clinical Trial

Abstract: BackgroundSchool refusal occurs in about 1–2% of young people. Anxiety and depression are considered to be the most common emotional difficulties for children who do not attend school. However, at present, no definitive treatment has been established for school refusal, although interventions such as cognitive behavioral therapy have been used. This paper reports a protocol for a cluster-randomized controlled trial of a mindfulness yoga intervention for children with school refusal.MethodsThis study is a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Foreign studies have shown that in the field of physiology and psychology, researchers have been able to perform various physiological tests such as electromyography, electroencephalogram and respiratory status before and after yoga training, and demonstrate that yoga training can reduce cortisol content in the body ( Amitani et al, 2022 ), relieve psychological pressure ( Schmalzl and Kerr, 2016 ), and improve people’s mental health ( Wang et al, 2020 ). Foreign scholar ( Daley et al, 2015 ) believes that yoga practice can make individuals feel happy and satisfied ( Kuyken et al, 2015 ), which is conducive to physical health.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign studies have shown that in the field of physiology and psychology, researchers have been able to perform various physiological tests such as electromyography, electroencephalogram and respiratory status before and after yoga training, and demonstrate that yoga training can reduce cortisol content in the body ( Amitani et al, 2022 ), relieve psychological pressure ( Schmalzl and Kerr, 2016 ), and improve people’s mental health ( Wang et al, 2020 ). Foreign scholar ( Daley et al, 2015 ) believes that yoga practice can make individuals feel happy and satisfied ( Kuyken et al, 2015 ), which is conducive to physical health.…”
Section: Discussionmentioning
confidence: 99%